THE ESSENTIAL ROLE OF ZINC IN GROWTH - Brandaoneto, J.; STEFAN, V; Mendonca, B. B.; Bloise, W.; Castro, AVB (Elsevier B.V., 1995)
Zinc is known to play a relevant role in growth and development. The basic mechanisms of action of this trace element are intimately linked to the structure and action of countless enzymes involved in many different metabolic processes. In this respect, when zinc specifically acts on cartilage growth it is involved in multiple enzymatic reactions which make this a multifactorial event. Thus, we may divide the actions of zinc into three distinct types: 1) action on taste and smell acuity, appetite regulation, and food consumption and regulation; 2) action on DNA and RNA synthesis stimulating a) cell replication and differentiation of chondrocytes, osteoblasts and fibroblasts; b) cell transcription culminating in the synthesis of somatomedin-C (liver), alkaline phosphatase, collagen and osteocalcin (bone), and c) protein, carbohydrate and lipid metabolism, that is intimately related to the mechanisms of smell, taste, appetite, and food consumption and utilization; 3) action on hormonal mediation by participating in a) GH synthesis and secretion in somatomammotroph cells, b) the action of GH on liver somatomedin-C production, and c) somatomedin-C activation in bone cartilage. In addition to these multiple functions, zinc also interacts with other hormones somehow related to bone growth such as testosterone, thyroid hormones, insulin, and vitamin D-3.On the basis of the above considerations, we conclude that the integration of these mechanisms contributes to the perfect physiological functioning of bone. Tn the presence of zinc deficiency, this homeostasis is impaired, causing the weight-height deficiency detected in several species studied, the human species in particular.
Keywords: ZINC; GROWTH; ENZYMATIC MECHANISMS; BONE METABOLISM; HORMONAL MEDIATION